Numerical analysis of masonry walls with horizontal chases using the Lattice Discrete element method (LDEM). (15th February 2022) - Fleith de Medeiros, Guilherme; Simonetti Milani, Alison; Lubeck, André; Mohamad, Gihad; Quispe Rodriguez, Rene; Eduardo Kosteski, Luis
Highlights: Numerical simulation of masonry walls with chases using the Lattice Discrete Element Method (LDEM) is presented. Experimental and numerical results of small-scale masonry walls with chases at their central part with depth of 20, 30 and 50% of its thickness were originally developed. In-plane strains, out-of-plane displacements, stresses and the characterization of the failure mechanism were done. In the 3D model in which the mortar joints were simulated, the pre-peak and post-peak behavior are better represented. The LDEM models are a good alternative for representing the behavior of the chased walls and to predict the strength, and failure mechanisms within this kind of structure. Abstract: This work presents the numerical simulation of small-scale masonry walls (1:5) with chases using the Lattice Discrete Element Method (LDEM). Experimental compression tests were originally developed using small-scale masonry walls with chase depth of 20, 30, and 50% of its thickness, with those cuts being located at their central part. To conduct the tests, in-plane strains; out-of-plane displacements; stresses and characterization of the failure mechanism (according to different chase depths) have been used to compare the proposed numerical models. The LDEM consists of discretizing the continuum by means of a 3D lattice of uniaxial elements with a constitutive law that carries the elastic and fracture properties of the material. Two types of models were proposed, one of them was simply supported and simplified 3D model. This model, where the wall was simulated using a homogeneous material, presented a good agreement with the experimental results for the pre-peak behavior of walls with cuts of 20 and 30% of their thickness. The failure mechanism observed in the numerical simulations was identical to the experimental counterpart; nonetheless, cracks appeared in random locations. In the simply supported 3D model, in which the mortar joints were simulated, the pre-peak and post-peak behavior were better represented. Moreover, the crack pattern was befitting with the tested small-scale masonry walls with chases of 20% and 30% of its thickness. The 3D wall model with a fixed support at one end and a simply pinned at the other end presented a good representation of the tested small-scale masonry walls with chases of 50% of its thickness. The LDEM models were a good alternative for representing the behavior of the chased walls and to predict the strength and failure mechanisms within this kind of structure.